Reconstruction of regional and national population using intermittent census-type data: the case of Portugal, 1527-1864 - Nuno Palma; Jaime Reis; Mengtian Zhang (European Historical Economics Society (EHES), 2019)
We offer a new methodology for the construction of annual population stocks over the very long run. Our method does not require the assumption of a closed economy, and can be used in situations in which local annual gross flows are obtainable. Combining gross flows with intermittent census-type data, it is possible to arrive at local, regional and national population stock estimates at annual frequencies. We provide an application to early modern and nineteenth century Portugal, using a large sample of parish-level statistics up to the first modern census of 1864. All six major regions of the country are considered. ghlight the effect of the second nature geography changes as well as protectionism on well-being. We use a novel database of Danish and Swedish real wages to investigate the impact of these changes on Scanian living standards by employing a difference in difference approach to show that wages fell more in Scania than those in surrounding regions in relation to the border change and associated protectionism.
Keywords: C65; J11; N33; 330; Border Demographic Reconstructions; Early Modern Portugal; Nineteenth Century Portugal